This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice solution!
A straightforward solution: x 3 + x 3 1 = 1 8 . We get a common denominator: x 3 x 9 + x 3 1 = 1 8 . We can rewrite the equation like so: x 6 − 1 8 x 3 − 1 = 0 . We can solve using u-substitution: u 2 − 1 8 u − 1 = 0 . We get a solution of u ≈ 1 8 . 0 6 . And 1 8 . 0 6 3 1 ≈ 2 . 6 . So to solve, 2 . 6 4 + 2 . 6 4 1 ≈ 4 7 . So the answer is 4 7 .
I think x 3 x 9 + x 3 1 = 1 8 results in x 6 − 1 8 x 3 − 1 = 0 .
Log in to reply
Oh yes, you're correct, I'll change it. Sorry about that.
Problem Loading...
Note Loading...
Set Loading...
⇒ x 3 + x 3 1 = 1 8
= ( x + x 1 ) ( x 2 + x 2 1 − 1 ) = 1 8
= ( x + x 1 ) [ ( x + x 1 ) 2 − 3 ] = 1 8
Let ( x + x 1 ) = a
= ( a ) ( a 2 − 3 ) = 1 8
= ( a ) ( a 2 − 3 ) = 3 × 6
∴ a = 3
⇒ x 4 + x 4 1
= [ ( x + x 1 ) 2 − 2 ] 2 − 2
= [ ( 3 ) 2 − 2 ] 2 − 2
= ( 7 ) 2 − 2
⇒ 4 7